Whatever Normal Is - St. Anthony, Jane (Book collections on Project MUSE., 2019)
In 1960s Minneapolis, seventeen-year-old Margaret and her best friends Grace and Isabelle contemplate whether having a job, car, and boyfriend are as fulfilling as they appear to be.